Crucial role of poly (ADP‐ribose) polymerase (PARP‐1) in cellular proliferation of Dictyostelium discoideum. Issue 5 (14th October 2018) - Jubin, Tina; Kadam, Ashlesha; Saran, Shweta; Begum, Rasheedunnisa
Abstract: The unicellular, as well as multicellular stages of Dictyostelium discoideum's life cycle, make it an excellent model system for cell type determination, differentiation, development, and cell death studies. Our preliminary results show the involvement of poly (ADP‐ribose) polymerase‐1 (PARP‐1) during D. discoideum growth by its constitutive downregulation as well as by its ortholog overexpression. The current study now analyzes and strengthens the role of the PARP‐1 ortholog in cellular proliferation of D. discoideum . ADPRT1A was knocked out (KO) from D. discoideum and studied for its effect on cell growth, cell cycle, morphology, and oxidative stress. The present findings show that ADPRT1A KO ( A KO) cells exhibited reduced cellular proliferation, stressed phenotype, and cell cycle arrest in G2‐M phase. Under oxidative stress, A KO cells exhibited slower growth and DNA damage. This is the first report where the involvement of ADPRT1A in growth in D. discoideum is established. Abstract : The current study provides the first evidence wherein ADPRT1A, poly (ADP‐ribose) polymerase‐1 ortholog is specifically shown to be involved in controlling cell growth and cell cycle in Dictyostelium discoideum .